Associations of sleep, coping, health and well being of Singapore’s police officers - Cai, Vanessa Jiaxin (2010)
This project examined sleep quality with coping, health and psychological resilience and well being of Singapore’s police officers. The association between poor sleep quality, lowered psychological resilience, health, coping and wellbeing was hypothesized. Self reported reports on stress-and-coping in the police work context obtained from a focus group discussion and included in a questionnaire together with psychological resilience, health and sleep quality measures, administered to 292 (237 male; 37 female) Singapore police officers mostly aged between 18-25. Factor analysis results grouped police coping strategies into problem and non-problem focused categories; high levels of sleep problems and stress were found; significant associations between poor sleep quality, poor health and well being, and use of non-problem focused coping strategies.